Two stellar populations with different metallicities in the low-mass globular cluster Gran 5 - Lim, Dongwook; Chun, Sang-Hyun; Lee, Young-Wook; Chung, Chul; Koch-Hansen, Andreas; Hong, Seungsoo (Astronomy and astrophysics, 2024)
Context. With the increasing number of discoveries of globular clusters in the inner Milky Way, the need for spectroscopic confirmation and further investigation of their stellar populations and chemodynamical properties has become crucial. Aims. Gran 5 is a newly reported low-mass globular cluster located close to the Galactic center, and it is thought to be an accreted object associated with the Gaia-Enceladus structure. This study aims to investigate the stellar populations of Gran 5 and their detailed chemical properties. Methods. We performed high-resolution near-infrared spectroscopy on seven stars in the field of Gran 5 using IGRINS on the Gemini-South telescope. Results. We identified six stars as cluster members and reveal that they are divided into two stellar populations with different metallicities, with mean [Fe/H] values of −0.76 dex and −0.55 dex, respectively. In addition, the chemodynamical properties of Gran 5 agree with those of in situ globular clusters. Conclusions. Our findings represent the first detection of two stellar populations with different metallicities in a low-mass globular cluster. This suggests that the metallicity variation in Gran 5 may have arisen from processes different from those in other globular clusters with metallicity variation, or that it may have lost a substantial amount of its initial mass during its evolution.